Update on the Financing of the Fund's Concessional Assistance and Debt Relief to Low-Income Member Countries. (Policy Papers; Policy Paper ;, 2010)
A new framework to facilitate mobilization of loan resources for the PRGT became effective in June 2010. It includes a voluntary encashment regime allowing claims of participating creditors to qualify as reserve assets; the issuance of PRGT notes; and a revised framework for borrowing in SDRs. Members have responded positively to the Managing Director's fund-raising request. Thirteen members have pledged about SDR 9.3 billion in additional loan resources, compared to the target of SDR 10.8 billion (including provision for a liquidity buffer to facilitate encashment). New loan and note purchase agreements totaling SDR 7.2 billion have been signed so far with nine lenders. Five of these borrowing agreements provide loan resources in SDRs. It remains important to mobilize additional loan resources to complete the financing package.